Mechanical and microstructural analysis on hydrogen-related fracture in a martensitic steel. (5th November 2019) - Shibata, Akinobu; Madi, Yazid; Okada, Kazuho; Tsuji, Nobuhiro; Besson, Jacques
Abstract: The present study quantitatively evaluated mechanical response of hydrogen-related fracture in the as-quenched martensitic steel and correlated it to crack propagation behavior analyzed by microstructure observations. The crack-growth resistance curves revealed that the hydrogen-related intergranular cracks propagated in a stable manner even when the diffusible hydrogen content was large. Fracture initiation toughness was decreased significantly by small amounts of diffusible hydrogen. With further increasing diffusible hydrogen content, however, the fracture initiation toughness did not change and remained almost constant. On the other hand, tearing modulus, corresponding to crack-growth resistance, decreased rather gradually with increasing diffusible hydrogen content. The microstructure observations confirmed that the hydrogen-related crack propagated discontinuously in a stepwise manner on a microscopic scale. Accordingly, it was proposed that the microscopic discontinuous crack propagation could be the possible reason for the stable crack propagation. Graphical abstract: Image 1 Highlights: Hydrogen-related fracture in as-quenched martensitic steel was studied. Fracture initiation toughness decreased significantly by small amounts of hydrogen. Crack-growth resistance decreased gradually with increasing hydrogen content. The hydrogen-related cracks propagated discontinuously on a microscopic scale. The discontinuous crack propagation could lead to stable crack propagation.